The impact of school attachment and parental involvement on the positive mental health of 2SLGBTQ + students during COVID-19 - Campbell, Christopher; Fraser, Ley; Peter, Tracey (Frontiers in Education, 2022)
On March 11th, 2020, the World Health Organization (WHO) declared the worldwide outbreak of COVID-19 as a pandemic. On the following day, the Ontario government (Canada’s most populous province) ordered all public schools to close. By Monday, March 16th, 2020, all public schools (and most private schools) in Canada announced plans to physically shutter schools, with a shift to remote and online learning to follow soon after. This unprecedented shift in learning environment for young Canadians came at a time when the onset of the COVID-19 pandemic was creating a challenging environment for the mental health of all Canadians. While all students may have struggled to cope, 2SLGBTQ + students faced an unusually complex shift, as their school and home environments may have contributed differentially to the social supports and acceptance (related to their 2SLGBTQ + identity or identities) that their cisgender heterosexual peers routinely experience in their social surroundings. In this paper, we explore the relationship between school attachment, parental involvement and positive mental health in 2SLGBTQ + youth using data collected as part of the Second Annual School Climate Survey on Homophobia, Biphobia, and Transphobia in Canadian Schools.